Comparison of incremental treadmill exercise and free range running - Crouter, S.; Foster, C.; Esten, P.; Brice, G.; Porcari, J. P. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The aim of this study was to compare physiological responses during incremental treadmill exercise and free range running. Methods: Fifteen competitive cross-country runners performed an incremental treadmill test and an unpaced 1-mile run on an indoor 200-m track. Physiological variables (VO2peak, HRpeak, VO2.HR-1peak, VEpeak) were measured using a portable metabolic analyzer. Blood lactate was measured post exercise. Outcome variables were analyzed with repeated measures ANOVA. Results: Although directionally similar to previous studies with cycle ergometry, the observed peak values (track vs treadmill) for VO2 (63.0 +/- 7.4 vs 61.9 +/- 7.2 mL.kg-1.min-1), VE (147 +/- 37 vs 144 +/- 30 L.min-1), HR (188 +/- 5 vs 189 +/- 7 beats.min-1), and VO2.HR-1 (22.1 +/- 4.4 vs 21.5 +/- 4.5) were not significantly different. The observed peak values for blood lactate (14.4 +/- 3.3 vs 11.7 +/- 3.0 mmol.L-1) were significantly (P < 0.05) different. Conclusions: The results are not in full agreement with previous findings from cycling studies with the exception of post exercise blood lactate. Whether this represents a fundamental lack of effect of free range exercise or is related to mode specificity remains to be determined.